Attitude of the Western states towards Lithuania {About the Doctoral Thesis and a it Defence of Ramojus Kraujelis "Attitude of the Western states towards occupation and annexation of Lithuania in the period of 1940-1953") - Algirdas Jakubčionis (Lietuvos Istorijos Studijos)
-